Study of ultrasound-guided ropivacaine combined with butorphanol continuous paravertebral block to prevent pain syndrome by evaluating ccl2 gene expression after radical mastectomy - Ji, Xiaochen; Cui, Wenbin; Shan, Shiqiang; Liu, Xiaomeng; Wang, Lixian; Zhang, Boya (Cellular and Molecular Biology, 2022)
This study aimed to investigate the clinical effect of ultrasound-guided ropivacaine combined with butorphanol continuous paravertebral block in preventing postoperative pain syndrome of breast cancer. For this purpose, 100 women treated for breast cancer from April 2018 to July 2019 were enrolled as research objects. Surgical procedures included local sentinel lymph node biopsy, mastectomy, sentinel lymph node biopsy for mastectomy, modified radical mastectomy, and implantation. The selected patients were randomly divided into two groups: control group (routine operation anesthesia; n = 50) and observation group (ultrasound-guided thoracic paravertebral block before induction of ropivacaine+butorphanol anesthesia; n = 50). The Real-time PCR technique was performed to evaluate CCL2 gene expression. VAS scores were recorded during the postoperative period. Compared with the control group, the observation group had lower VAS scores at six h, 24h, and 48h (P<0.05). The pain effect of the observation group was less than that of the control group. The observation group had better analgesic effects after anesthesia. The observation group had a lower incidence of pain syndrome at the 6th, 8th, and 12th months (P<0.05), and the incidence of pain syndrome in the two groups decreased with the extension of time. The observation group had lower levels of related factors (P<0.05), and the observation group had lower traumatic stress responses. The protein expression of IL-6, IL-17, and CRP in the observation group was lower than that in the control group (P<0.05). The results of CCL2 gene expression also showed that gene expression in the control group increased significantly (P=0.0047). Since the expression of this gene is one of the factors that stimulate pain signals in the body, the method used in the present study was able to reduce the amount of pain significantly. Therefore, the combination of ropivacaine combined with butorphanol ultrasound-assisted paravertebral block can reduce the intensity of postoperative pain in patients with breast cancer surgery, decrease the incidence of pain syndrome, and increase pain tolerance.